The Dead Sea scrolls : the riddle debated - Star, Leonie (Crows Nest, N.S.W : ABC Enterprises, 1991)
Publisher's description: On 8 April 1990, Palm Sunday, a documentary entitled The Riddle of the Dead Sea Scrolls was screened nationally on ABC Television. Based on the radical theories of Dr Barbara Thiering about the origins of Christianity, it caused a minor uproar in the press even before it went to air. The response after the broadcast was extraordinary. Almost 250 letters to Dr Thiering revealed that her views wer perhaps more acceptable than the reaction of church leaders and academics might have indicated. Many who watched the televised debate about the documentary also felt that it had not allowed Thiering to respond adequately to her critics. In The Dead Sea Scrolls: the Riddle Debated Leonie Star presents the main issues in easily comprehensible form, with especially written pieces by Dr Thiering. The author contrasts the criticism and reactions of church leaders, scholars and ordinary people, setting out opposing arguments in detail and giving readers the information to make their own judgment on this contentious subject.
1. Background -- 2. Methodology -- 3. Miracles -- 4. The resurrection -- 5. Scholarly and religious responses -- 6. The Australian Broadcasting Corporation -- 7. Modern Christianity.
"The controversy surrounding Dr Barbara Thiering's views on the Dead Sea scrolls and Christianity as seen in the ABC TV documentary." -- Cover.
Includes bibliographical references (p. 143-146)
Keywords: Dead Sea scrolls -- Relation to the New Testament; Christianity -- Origin